2016
DOI: 10.1109/access.2016.2604360
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Positioning Based on Millimeter Wave Device to Device Communications

Abstract: Current generation mobile wireless communication networks are not suitable for real-time positioning applications because timing information is not readily available. Fifth generation (5G) cellular networks provide device to device real-time communications which can be used for real-time positioning. Millimeter-wave (mmWave) transmission is regarded as a key technology in 5G networks. In this paper, several 73-GHz mmWave waveforms are investigated. A new threshold selection algorithm for energy detector-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Cui et al [34] studied a real-time positioning based on the D2D real-time communication, which will be reliable in future 5G cellular networks. The ranging and positioning performance were evaluated with four impulse radio waveforms.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Cui et al [34] studied a real-time positioning based on the D2D real-time communication, which will be reliable in future 5G cellular networks. The ranging and positioning performance were evaluated with four impulse radio waveforms.…”
Section: Related Workmentioning
confidence: 99%
“…By exploring physical layer information 95% LOS was identified in [52]. Cui et al [34] showed how to detected actual TOA from an NLOS / multipath channel from received signal energy. According to them in a multipath channel with a low signal to noise ratio, some low energy level value may appear before the maximum energy value.…”
Section: Toa Based Distance Determinationmentioning
confidence: 99%
“…In [33], the optimal power allocation and codeword rate design for secure relay communications were performed in Internet of Things (IoT) networks. For real-time positioning in millimeter wave D2D communications, a new threshold selection algorithm for energy detector-based ranging was proposed by employing a dynamic threshold based on an artificial neural network [34]. In [35], a new channel assignment method was proposed in wireless mesh networks.…”
Section: Introductionmentioning
confidence: 99%
“…Contrariwise, when an indoor space or in an urban canyon is considered, the GNSS positioning in not possible and it is mandatory to overcome this issue considering different techniques and sensors. In recent years, some indoor location-based services (LBSs) have been developed integrating different technologies and measurements [22], such as cameras [27], infrared (Kinect), ultrasound [20], WLAN/Wi-Fi [6], RFID [23], mobile communication [10], and so forth are examples of the technologies that the scientific community has put at the service of indoor locations. Despite the ample panorama of solutions, mass market applications for indoor positioning require the use of embedded sensors in commercial smartphone without supplementary physical components.…”
Section: Indoor Scenariosmentioning
confidence: 99%